2023
DOI: 10.3389/fmicb.2023.1236208
|View full text |Cite
|
Sign up to set email alerts
|

Detection of blaCTX-M and blaDHA genes in stool samples of healthy people: comparison of culture- and shotgun metagenomic-based approaches

Edgar I. Campos-Madueno,
Claudia Aldeia,
Vincent Perreten
et al.

Abstract: We implemented culture- and shotgun metagenomic sequencing (SMS)-based methods to assess the gut colonization with extended-spectrum cephalosporin-resistant Enterobacterales (ESC-R-Ent) in 42 volunteers. Both methods were performed using native and pre-enriched (broth supplemented with cefuroxime) stools. Native culture screening on CHROMID® ESBL plates resulted in 17 positive samples, whereas the pre-enriched culture (gold-standard) identified 23 carriers. Overall, 26 ESC-R-Ent strains (24 Escherichia coli) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Notably, direct culture-based analyses on MacConkey II and Columbia sheep blood agar plates (Becton-Dickinson) revealed that disinfected pears were contaminated with Bacillus cereus [~3 × 10 1 colony forming units (CFU)/mL], whereas dry food contained ,afaD,chuA,fimH,fimC,gad,hra,iha,iss,kpsE,kpsMII_K5,ompT,papA_ F43,sat,senB,traT fimH,gad,terC,yehA,yehB,yehC,yehD csgA,gad,hra,irp2,terC Moraxella osloensis and Micrococcus luteus (~2-5 × 10 2 CFU/mL); the oat substrate was constantly negative. Moreover, the three types of food were regularly screened for the presence of extended-spectrum cephalosporin-resistant (ESC-R)-Ent using an overnight broth enrichment and selective agar plates as previously done (Endimiani et al, 2020;Campos-Madueno et al, 2023a). As a result, no food used throughout experiments resulted contaminated with ESC-R-Ent (data not shown).…”
Section: Colonization Experimentsmentioning
confidence: 99%
“…Notably, direct culture-based analyses on MacConkey II and Columbia sheep blood agar plates (Becton-Dickinson) revealed that disinfected pears were contaminated with Bacillus cereus [~3 × 10 1 colony forming units (CFU)/mL], whereas dry food contained ,afaD,chuA,fimH,fimC,gad,hra,iha,iss,kpsE,kpsMII_K5,ompT,papA_ F43,sat,senB,traT fimH,gad,terC,yehA,yehB,yehC,yehD csgA,gad,hra,irp2,terC Moraxella osloensis and Micrococcus luteus (~2-5 × 10 2 CFU/mL); the oat substrate was constantly negative. Moreover, the three types of food were regularly screened for the presence of extended-spectrum cephalosporin-resistant (ESC-R)-Ent using an overnight broth enrichment and selective agar plates as previously done (Endimiani et al, 2020;Campos-Madueno et al, 2023a). As a result, no food used throughout experiments resulted contaminated with ESC-R-Ent (data not shown).…”
Section: Colonization Experimentsmentioning
confidence: 99%